Ego-driven Politics and Its Impact on Pakistan’s Regional and Global Diplomacy - Khan, Muhammad Saeed; Hayat, Khizar; Afzal, Afzaal; Riaz, Ahsan; Zumard, Ayesha (Pakistan Journal of Humanities and Social Sciences, 2025)
In the contemporary world, a prominent characteristic of international relations is ego-driven politics, which has attained a defining role and significantly influences diplomatic engagements and a country's foreign policy choices. In reference to Pakistan, personal political motives and leadership styles have played a pivotal role in the formulation of foreign policy, which affects its relations with neighbors and strategic partners such as China, the United States, Iran, and Turkey. To study this phenomenon, the mixed methods research approach is employed in this research to combine qualitative case studies of leadership decisions in Pakistan with quantitative analysis of the data on diplomatic interactions, trade volumes, and foreign policy stability scores. In the study, qualitative data includes case studies of major diplomatic engagements, and the quantitative data is based on statistical assessments drawn from consistency scores and index rankings of regional and global diplomacy. This study also evaluates how diplomatic approaches change under the influence of ego-driven leadership and result in policy shifts, fluctuating alliances, and strategic recalibrations in Pakistan. It also assesses events that resulted in policy shifts, policy incoherence, discordant diplomatic ties, and retaliatory foreign policy strategies due to personalized decision-making, which often prioritizes individual political motives over national interest. The study further emphasizes the challenges created by such leadership styles in sustaining long-term diplomatic stability. The paper concludes by highlighting the need for institutionalized foreign policy and a methodological framework to ensure geopolitical equilibrium, diplomatic coherence, and a more systematic approach to Pakistan’s regional and global diplomatic ties.